Biomarker and Carbon Isotope Composition of the Oil Stains from the North Hadramaut High Area of Eastern Yemen: Implications on the Nature of Organic Matter Input and Their Characteristics - Hakimi, M.H. (Springer Science and Business Media Deutschland GmbH, 2022)
Five core sandstone and carbonate rock samples from the Cretaceous Harshiyat Formation containing oil stains were collected from two wells in the North Hadramaut High area (eastern Yemen) and geochemically analyzed by their sterane and terpane biomarker and stable carbon isotope (Î´13C) compositions. This paper studied the geochemical characteristics of the oil stains and their relation to probable potential source rocks. The source rock characteristics include the origin of organic matter input; redox depositional conditions, lithology, and degree of thermal maturity were investigated. The saturated and aromatic hydrocarbon fractions of the analyzed oil stain samples have Î´13C values in the range of â 26.5â° â â 28.6â° and â 26.3â° â â 26.7â°, respectively. These Î´13C values indicate that the oil stain samples originated from a mixed organic matter input in their source rock. The presence of mixed marine and terrestrial organic matter in the source rock is further concluded from biomarker distributions of n-alkane, isoprenoid, terpane, and sterane. These biomarkers and their ratio parameters suggest that the analyzed oil stain samples were sourced from clay-rich rock deposited in marine-reducing environmental conditions and likely contained mixed planktonic/bacterial organic matter and land plant inputs. Both saturated and aromatic maturity biomarkers suggest that the analyzed oil stains were from a mature source rock, equivalent to a moderate to peak-mature oil window. The environmental biomarker indicators of the studied oil stain samples correlated well with the shales in the Late Cretaceous Harshiyat Formation in the onshore Jiza-Qamar Basin (eastern Yemen), indicating that the analyzed oil stains were generated from a mature Harshiyat source rock in the onshore Jiza-Qamar Basin and subsequently migrated into the Cretaceous Harshiyat sandstone and limestone reservoirs in the North Hadramaut High area (eastern Yemen) through normal faults system. Â© 2021, King Fahd University of Petroleum & Minerals.